Respuesta :

Answer:

a) (x+6)(x-1)

b) (x+8)(x-5)

c) (x+3)(x-10)

Step-by-step explanation:

The final answer would always have to be two brackets with x and the relevant variables.

x²: You know the possible factors that can be multiplied together would be x and x. Each factor would have to be in different brackets, so we get (x + smth else)(x +smth else)

When factorising quadratic expressions, you need to find the correct pair of factors, that when multiplied together, becomes the constant of the expression. They also need to become the middle term when they are multiplied with the term in the bracket and then added together.

Possible factors for a):

1. 1 × 6 = 6

2. 2 × 3 = 6

You know 1 - 6 = -5, so we shall use the factors 6 and 1.

(x+6)(x-1) = x² -x + 6x - 6

              = x² + 5x - 6

Thus, (x+6)(x-1) is the answer.

Possible factors for b):

1. 1 × 40 = 40

2. 2 × 20 = 40

3. 4 × 10 = 40

4. 5 × 8 = 40

You know 8 - 5 = 3, so we shall use the factors 8 and 5.

(x+8)(x-5) = x² -5x + 8x - 40

               = x² + 3x - 40

Thus, (x+8)(x-5) is the answer.

Possible factors for c):

1. 1 × 30 = 30

2. 2 × 15 = 30

3. 3 × 10 = 30

4. 5 × 6 = 30

You know 3 - 10 = -7, so we shall use the factors 3 and 10.

(x+3)(x-10) = x² -10x + 3x - 30

               = x² - 7x - 40

Thus, (x+3)(x-10) is the answer.

a)

x² - 5x - 6

= x² + x - 6x - 6

= x(x + 1) -6(x + 1)

= (x - 6) (x + 1)

b)

x² + 3x - 40

= x² + 8x - 5x - 40

= x(x + 8) -5(x + 8)

= (x - 5) (x + 8)

c)

x² - 7x - 30

= x² - 10x + 3x - 30

= x(x - 10) + 3(x - 10)

= (x + 3) (x - 10)

ACCESS MORE